2018
DOI: 10.1093/neuros/nyy127
|View full text |Cite
|
Sign up to set email alerts
|

External Ventricular Drain and Hemorrhage in Aneurysmal Subarachnoid Hemorrhage Patients on Dual Antiplatelet Therapy: A Retrospective Cohort Study

Abstract: Patients with aSAH who receive stent-assisted coiling or flow diversion are at higher risk for radiographic hemorrhage associated with EVD placement. The timing between EVD placement and DAPT initiation does not appear to be of clinical significance. Stenting and flow diversion remain viable options for aSAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 11 publications
2
20
2
Order By: Relevance
“…Madaelil et al reported similar rates of 57% and 2% (p=0.001) for these two groups, a finding which agrees with the existing literature that aneurysm size is a risk factor for rebleeding 18. Cohen et al emphasized the need to consider placing an external ventricular drain (EVD) prior to FD placement to lower the risk of hemorrhagic complications which are more likely to occur when an EVD is placed under dual antiplatelet therapy 19–21. In our study 20 patients (45%) had a ventriculostomy prior to FD placement.…”
Section: Discussionsupporting
confidence: 88%
“…Madaelil et al reported similar rates of 57% and 2% (p=0.001) for these two groups, a finding which agrees with the existing literature that aneurysm size is a risk factor for rebleeding 18. Cohen et al emphasized the need to consider placing an external ventricular drain (EVD) prior to FD placement to lower the risk of hemorrhagic complications which are more likely to occur when an EVD is placed under dual antiplatelet therapy 19–21. In our study 20 patients (45%) had a ventriculostomy prior to FD placement.…”
Section: Discussionsupporting
confidence: 88%
“…Despite of some minor hemorrhages from postinterventional invasive procedures under antiplatelet regimes, our findings confirmed previous findings that placement of EVDs and/or ICP probes was not associated with an increased risk of severe intracranial hemorrhage [29]. In contrast, stent-assisted coiling or flow diverters were associated with an increased risk for clinically significant PHs [15]. In such cases, sAP is frequently extended with newer antiplatelet agents such as tirofiban.…”
Section: Post-interventional Surgery and Pphsupporting
confidence: 87%
“…Although no hemorrhage was detected in our 4 cases, the risk of procedurerelated hemorrhage should be taken seriously. However, Hudson et al (22) suggested that both antiplatelet-associated hemorrhaging and the timing between external ventricular drain placement and DAPT initiation did not appear to be clinically significant.…”
Section: Stent Deploymentmentioning
confidence: 99%